Animal Models of Diabetes-Associated Renal Injury - Zahra Samadi Noshahr; Hossein Salmani; Abolfazl Khajavi Rad; Amirhossein Sahebkar (Journal of Diabetes Research)
Diabetic nephropathy (DN) is the main factor leading to end-stage renal disease (ESRD) and subsequent morbidity and mortality. Importantly, the prevalence of DN is continuously increasing in developed countries. Many rodent models of type 1 and type 2 diabetes have been established to elucidate the pathogenesis of diabetes and examine novel therapies against DN. These models are developed by chemical, surgical, genetic, drug, and diet/nutrition interventions or combination of two or more methods. The main characteristics of DN including a decrease in renal function, albuminuria and mesangiolysis, mesangial expansion, and nodular glomerulosclerosis should be exhibited by an animal model of DN. However, a rodent model possessing all of the abovementioned features of human DN has not yet been developed. Furthermore, mice of different genetic backgrounds and strains show different levels of susceptibility to DN with respect to albuminuria and development of glomerular and tubulointerstitial lesions. Therefore, the type of diabetes, development of nephropathy, duration of the study, cost of maintaining and breeding, and animals’ mortality rate are important factors that might be affected by the type of DN model. In this review, we discuss the pros and cons of different rodent models of diabetes that are being used to study DN.